Health outcomes and budget impact projection of anti-PD-(L)1s in cancer care in Portugal - Costa, Luís; Alexandre, Teresa; Mansinho, André; Sousa, Rita; Vieira, Cláudia; Hughes, Robert; Roediger, Alexander; Pereira, Sónia Matos; Araújo, António (Frontiers in Public Health, 2023)
Introduction: PD-[L]1 inhibitors revolutionized cancer treatment but challenge the affordability of health systems. This policy-focused model aimed to estimate the health and budget impact of anti-PD-(L)1s in Portugal and inform current discussions. Materials and Methods: The Health Impact Projection (HIP) model estimates clinical (life years, progression-free survival [PFS] years, and quality-adjusted life years [QALY] gained and adverse events [AEs] incurred) and economic (direct and indirect costs) outcomes in a world where cancer patients are initiating treatment with standard-of-care (SOC) versus SOC plus anti-PD-(L)1s over a 3-year time horizon. Indications included adjuvant and metastatic melanoma, non‐small cell lung cancer (first and second line), metastatic triple-negative breast cancer, head and neck cancer, urothelial carcinoma, and renal cell carcinoma. Model inputs were based on publicly available literature data and expert opinion. Results: The model estimated that, over 3 years, 7,773 patients would be treated with anti‐PD‐(L)1s, realizing a gain of 4,787 life years, 6,901 PFS years, and 4,214 QALYs and avoiding 399 AEs. The introduction of anti‐PD‐(L)1s had a projected average annual impact of ≈ €108 million and a share of 20% of total cancer medicines expenditure and 0.6% of total healthcare expenditure in 2021. Although higher disease management costs are expected for patients living longer with anti‐PD‐(L)1s and drug acquisition costs are considerable, that is partially offset by a reduction in end-of-life costs (€611,092/year) and costs associated with patient productivity lost to cancer (€9,128,142/year). Discussion: This model highlights the significant survival and QoL benefit of anti-PD-(L)1s for cancer patients in Portugal, with a relatively low increased cost in total healthcare expenditure.